Banyuwangi Women in Political and Social Struggle - Maulani, Diki (CV. Sekawan Siji, 2024)
Unsustainable tourism growth can result in significant environmental damage, including pollution and loss of resources, which are major contributors to climate change. To ensure the sustainability of tourism, there needs to be a concept that can support this goal, one of which is the concept of green tourism. This research uses a qualitative approach, searching for related literature from academic sources such as books, scientific journals and trusted articles. Banyuwangi's political and social environment offers women a complex and varied range of opportunities and challenges. While there are barriers such as gender stereotypes and cultural barriers that prevent women from occupying leadership positions, there are also networks of support and opportunities for women to succeed.